Caliph of Cairo: Al-Hakim bi-Amr Allah, 996 - 1021 - Walker, Paul E. (American Univ. in Cairo Press, 2009)
"One night in the year 411/1021, the powerful ruler of the Fatimid empire, al-Hakim bi-Amr Allah, rode out of the southern gates of Cairo and was never seen again. Was the caliph murdered, or could he have decided to abandon his royal life, wandering off to live alone and anonymous? Whatever the truth, the fact was that al-Hakim had literally vanished into the desert." "Yet al-Hakim, through shrouded in mystery, has never been forgotten. To the Druze, he was (and is) God, and his disappearance merely indicated his reversion to non-human form. For Ismailis, al-Hakim was the sixteenth imam, descended from the Prophet, and infallible. Jews and Christians, by contrast, long remembered him as their persecutor, who ordered the destruction of many of their synagogues and churches. Using all the tools of modern scholarship, Paul Walker offers the most balanced and engaging biography yet to be published of this endlessly fascinating individual."--Jacket